Implementation of sheet-pipe subsurface drainage system in Indonesia: Enhancing soil aeration and water management - Saptomo Satyanto Krido; Purwanto M. Yanuar J.; Arif Chusnul; Setiawan Budi Indra; Tamura Koremasa; Matsuda Hiroshi (BIO Web of Conferences)
Since 2017, the installation of the Sheet-pipe system in Indonesia has marked a significant development. This initiative, a collaboration between the Ministry of Agriculture and a Japanese construction company, aims to improve water management in rice paddies. The system was specifically installed at the Sukamandi Rice Research Center in West Java, covering an area of 3600m2. Seven parallel sheet-pipe lines, each 100 meters in length and 40 cm deep, were laid out. These lines were consolidated into three drainage outlets regulated by valves. The primary goal was to evaluate the drainage capacity and land drainage modulus using the sheet-pipe system. Measurements of the drainage water exiting each pipe were taken using gravimetric methods at specific time intervals under saturated soil conditions. The results indicated a total drainage rate ranging from 0.396 l/s to 1.431 l/s. The maximum drainage rate per sheet-pipe lane was 0.20 l/s, and the drainage modulus was 275 m3 day−1 ha−1. These findings illustrate the efficiency of the sheet-pipe system in facilitating water reduction to the sheet-pipe depth, thereby enhancing soil aeration.